ダイ36ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1995 - 佐藤, 尚志; サトウ, タカシ; 吉見, 英史; ヨシミ, ヒデシ; 竹川, 元章; タケカワ, モトアキ; 宮内, 誠司; ミヤウチ, セイジ; 中村, 辰男; ナカムラ, タツオ; Satoh, Takashi; Yoshimi, Hideshi; et al. (1999)
P(論文) この報告は, 第36次南極地域観測隊気象部門が1995年2月1日から1996年1月31日まで昭和基地及びドームふじ観測拠点において行った気象観測の結果をまとめたものである。ドームふじ観測拠点では, これまで日本の観測隊が経験したことのない極低温下で, 通年の地上気象観測が初めて行われた。昭和基地での観測方法・設備・統計計算等は第35次観測隊とほぼ同じである。ドームふじ観測拠点での地上気象観測方法は昭和基地と同様である。越冬期間中特記される気象現象としては次のものが挙げられる。1) 昭和基地でA級ブリザードの襲来により, 10月としては過去最高の最大瞬間風速49.0m/sを記録した。2) 昭和基地で7年連続の大規模なオゾンホールを観測し, 観測開始以来最低の日代表値128m atm-cmのオゾン全量を, 10月6日に記録した。3) ドームふじ観測拠点で, 8月18日に日本の南極観測隊史上の最低気温-79.6℃を観測した。 This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 36th Japanese Antarctic Research Expedition (JARE-36) from 1 February 1995 to 31 January 1996 at Syowa Station and Dome Fuji Station. The first overwintering team at Dome Fuji Station had conducted year-round surface synoptic observations under extremely cold conditions that had not been experienced by any other Japanese projects before. The method of observations, instruments and statistical calculation at Syowa Station were the same as those of the JARE-35 observation team. At Dome Fuji Station, similar surface observation techniques were used. The principal topics in the period of JARE-36 were as follows. 1) In the "A" class blizzard which hit Syowa Station in October, 49.0m/s maximum gust wind speed was recorded, the strongest for October in history. 2) An Antarctic ozone hole of large scale was observed for the seventh successive years at Syowa Station. The lowest daily total ozone was 128m atm-cm on 6 October 1995,the lowest in the historical record of Syowa Station. 3) The lowest temperature of -79.6℃ for this period was marked on 18 August 1995 at Dome Fuji Station, the lowest in the history of the Japanese Antarctic Research Expedition. departmental bulletin paper